(untitled) - Hennig, Willi (Chicago, Ill., 1999)
Phylogenetic Systematics", first published in 1966, marks a turning point in the history of systematic biology. Willi Hennig's influential synthetic work, arguing for the primacy of the phylogenetic system as the general reference system in biology, generated significant controversy and opened possibilities for evolutionary biology that are still being explored.
Keywords: Animals,Động vật; Classification,Phân loại